PENGARUH BIOLOGICAL ASSET INTENSITY, KEPEMILIKAN MANAJERIAL, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN ASET BIOLOGIS PADA SEKTOR AGRIKULTUR - Davit Andryan Pakpahan; Selfi Afriani Gultom; Lili Sri Ayu Harahap; Ilham Hidayah Napitupulu; Eli Safrida (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study examines the effect of biological asset intensity, managerial ownership, and profitability on biological asset disclosure in agricultural companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative approach with secondary data from annual reports and financial statements, the study analyzes 10 companies selected through purposive sampling, resulting in 50 observations. Data are analyzed using descriptive statistics and multiple linear regression with SPSS 27. The results show that biological asset intensity has a positive and significant effect, managerial ownership has no significant effect, and profitability has a negative and significant effect on biological asset disclosure.